Pembrolizumab plus GX-188E therapeutic DNA vaccine in patients with HPV-16-positive or HPV-18-positive advanced cervical cancer: interim results of a single-arm, phase 2 trial. Issue 12 (December 2020) - Youn, Jin Won; Hur, Soo-Young; Woo, Jung Won; Kim, Yong-Man; Lim, Myong Cheol; Park, Sang Yoon; Seo, Sang Soo; No, Jae Hong; Kim, Byoung-Gie; Lee, Jae-Kwan; Shin, So Jin; Kim, Kyungun; et al.
Summary: Background: Survival outcomes for patients with recurrent or advanced cervical cancer are poor. Pembrolizumab has been approved for the treatment of recurrent or metastatic cervical cancer, with an overall response rate of 14·3%. GX-188E vaccination has been shown to induce human papillomavirus (HPV) E6-specific and E7-specific T-cell responses and cervical lesion regression in patients with cervical precancer. We aimed to investigate whether a combination of GX-188E therapeutic DNA vaccine plus pembrolizumab showed antitumour activity against recurrent or advanced cervical cancer. Methods: In this open-label, single-arm, phase 2 trial, patients with recurrent or advanced, inoperable cervical cancer, who were aged 18 years or older with Eastern Cooperative Oncology Group performance status of 0 or 1 and histologically confirmed recurrent or advanced HPV-positive (HPV-16 or HPV-18) cervical cancer, and who had progressed after available standard-of-care therapy were recruited from seven hospitals in South Korea. Patients received intramuscular 2 mg GX-188E at weeks 1, 2, 4, 7, 13, and 19, with one optional dose at week 46 that was at the investigator's discretion, and intravenous pembrolizumab 200 mg every 3 weeks for up to 2 years or until disease progression. The primary endpoint was the overall response rate within 24 weeks assessed by the investigator using Response Evaluation Criteria in Solid Tumors version 1.1 in patients who received at least 45 days of treatment 45 days of treatment with at least one post-baseline tumour assessment, and this is the report of a planned interim analysis. This trial is registered with ClinicalTrials.gov, NCT03444376 . Findings: Between June 19, 2018, and March 20, 2020, 36 patients were enrolled and received at least one dose of the study treatment. 26 patients were evaluable for interim activity assessment, with at least one post-baseline tumour assessment at week 10. At the data cutoff date on March 30, 2020, median follow-up duration was 6·2 months (IQR 3·5–8·1). At 24 weeks, 11 (42%; 95% CI 23-63) of 26 patients achieved an overall response; four (15%) had a complete response and seven (27%) had a partial response. 16 (44%) of 36 patients had treatment-related adverse events of any grade and four (11%) had grade 3–4 treatment-related adverse events. Grade 3 increased aspartate aminotransferase, syncope, pericardial effusion, and hyperkalaemia, and grade 4 increased alanine aminotransferase were reported in one patient each. No treatment-related deaths were reported. Interpretation: Treatment with GX-188E therapeutic vaccine plus pembrolizumab for patients with recurrent or advanced cervical cancer was safe and treatment-related adverse events were manageable. This combination therapy showed preliminary antitumour activity in this interim analysis, which could represent a new potential treatment option for this patient population. This trial is ongoing. Funding: National OncoVenture.